In Vitro Antihyperlipidemic Potential of Triterpenes from Stem Bark of Protorhus longifolia - Mosa, Rebamang A.; Naidoo, Javan J.; Nkomo, Fezile S.; Mazibuko, Sithandiwe E.; Muller, Christo J. F.; Opoku, Andy R. (Planta Medica, 2014)
Two lanostane triterpenes, 3β-hydroxylanosta-9,24-dien-21-oic acid (1) and methyl-3β-hydroxylanosta-9,24-dien-21-oate (2), were isolated from the stem bark of Protorhus longifolia. Their structures were deduced on the basis of spectroscopic analysis (NMR, HRMS, IR). This study investigated the in vitro anti-adipogenic activity of the two triterpenes. Their inhibitory activity was evaluated on selected lipid digestive enzymes (pancreatic lipase and cholesterol esterase). The inhibitory activity of the compounds on hormone-sensitive lipase and their ability to bind bile acids were also evaluated. The effect of the compounds on glucose uptake in C2C12 muscle cells and 3T3-L1 adipocytes, and on triglyceride accumulation in 3T3-L1 adipocytes was investigated. The triterpenes effectively inhibited the activities of the enzymes with IC50 values ranging from 0.04 to 0.31 mg/mL. The compounds showed a high affinity for secondary bile acids. Both compounds stimulated glucose uptake in C2C12 muscle cells and 3T3-L1 adipocytes. Compound 1 significantly reduced triglyceride accumulation in mature differentiated 3T3-L1 adipocytes. It is apparent that these lanostane triterpenes enhance glucose uptake and suppress adipogenesis, which together with their inhibitory effects on lipid digestive enzymes suggests that they have antihyperlipidemic potential.
Keywords: Protorhus longifolia; Anacardiaceae; triterpenes; adipogenesis; antihyperlipidemic activity